Online learning and teaching: Managing the experience of online teaching - Mohamed, Abdul Halim; Dzakiria, Hisham; Kassim, Azilah; Yusoff, Nuraini (The University of International Business & Economics (UIBE), 2000)
The declining standard of english is obvious at tertiary level in most local federally-funded universities in Malaysia. This worsening condition of the target language among varsity student is quite noticeable.This would definitely bring certain impact on companies attitudes of hiring today's graduates, as they are not competent users of the language.As students need opportunies to practise the target language,the internet use in teaching English for specific Purpose (ESP)should be encouraged among education providers and educators.The network of networks the internet, is seen as a new learning tool in providing rich experiential active learning and opportunities to practice the target language.This computer-mediated communication (CMC)tool is versatile not only in asisting them to be competent users but also in providing employable skills for more challenging jobs in the new millennium.As resourceful tool,the internet can be fully "exploited" in producing graduates who are knowledgeable and computer-literate.To be good language learners, the use of online teaching of English can boost students morale and provide opportunities for them to learn the language integratively.This paper is a small-scale research investigating students' use of a free web-based learning in language teaching.This paper looks at how a group of students develop to become competent users of ESP at Universiti Utara Malaysia (UUM). The paper also looks at the perceptions, knowledge and skills of the students involved after getting the exposure of online learning for a semester.The findings indicate that there is a large significant increase of language production, written and spoken language, among students engaging on the use of the language via computer. The study indicates a strongincrease between traditional classroom teaching and online teaching.Besides, students' morale and motivation and motivation of learning the language is also discussed as the results of the online learning and teaching of English.